Analysis of Current Status and Regulatory Promotion for Incineration Bottom Ash Recycling in Taiwan - Chi-Hung Tsai; Yun-Hwei Shen; Wen-Tien Tsai (Resources, 2020)
Incineration is the most important technology for treating municipal solid waste (MSW) and industrial waste in Taiwan. Currently, there are 24 large-scale MSW incineration plants operated to generate about 1.2 million metric tons of residual ash (mostly bottom ash) based on approximately 6.5 million metric tons of waste incinerated yearly. To reduce the depletion of non-renewable resources under the circular economy principle, the recycling of MSW incineration bottom ash (IBA) as recycled aggregate in concrete and construction applications has been progressed in recent years around the world. According to the official database, the trend analysis of MSW generation and treatment, electricity power and IBA generation from the MSW incineration plants over the past decade (2010–2019) was performed in this work. It showed an increased power generation, growing from 0.485 kWh/kg in 2010 to 0.530 kWh/kg in 2019. In 2019, 2738 GWh of power was sold to Taipower (one of the state-owned companies in Taiwan) for electricity grid connection, gaining income of about NT$ 5,089,383,000 (≈US$ 172,520,000) at an average rate of 1.86 NT$/kWh (0.063 US$/kWh). On the other hand, the ratios of incineration bottom ash (IBA) generation to refuse incinerated indicated a decreasing trend due to the increased operation efficiencies of MSW incineration plants. Based on the revised regulations implemented on 18 May 2020, the regulatory measures for promoting IBA recycling in Taiwan were promulgated to valorize it for the production of recycled aggregate under rigorous requirements for prevent it from polluting the environment.